Comparison between 4 weeks passive static stretching and proprioceptive neuromuscular facilitation programmes on neuromuscular properties of hamstring muscles: a randomised clinical trial. (2nd March 2020) - Cini, Anelize; de Vasconcelos, Gabriela Souza; Soligo, Milena Caumo; Felappi, Cassiele; Rodrigues, Rodrigo; Aurélio Vaz, Marco; Lima, Cláudia Silveira
Abstract : Background/aims: Studies have shown the efficacy of stretching to increase the hip flexion range of motion but studies regarding its effects are not unanimous about the most efficient technique. The aim of this study was to compare the effect of two stretching techniques on the neuromuscular properties of the hamstring muscles. Methods: A total of 18 women (aged 24 ± 2.52 years old) participated, and were divided into three groups: a control group, a passive static stretching group and a propioceptive neuromuscular facilitation stretching group. Evaluations of variables of the hamstring muscles were performed before and after the training period. The intervention was carried out for 30 seconds, three times a week for a total of 4 weeks. Results: A significant difference was found in the range of motion in the passive static stretching group (pre=80.8° [±11.0] and post=94.5° [±10.2]; t (5)=−3.755; P =0.013) and in concentric torque (passive static stretching group – pre=66.3 Nm [±12.9] and post=70.0 Nm [±8.1]; t (5)=−1.267; P =0.023; propioceptive neuromuscular facilitation stretching group – pre=79.1 Nm [±12.7] and post=83.5 Nm [±11.6]; t (5)=−1.917; P =0.014; control group – pre=71.1 Nm [±10.1] and post=74.1 Nm [±14.6]; t (5)=−1.275; P =0.003). Conclusions: Passive static stretching was superior to propioceptive neuromuscular facilitation when comparing the increase range of motion in hip flexion, even without neural and structural changes in hamstring muscles after a 4-week period.